1975
DOI: 10.1093/geronj/30.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory Grief and Aged Widows and Widowers

Abstract: The purpose of this investigation was to explore the preventive value of anticipatory grief on the medical adjustment of the aged bereaved. Data were collected for 81 surviving widows and widowers 6 mo. after their loss. Sixteen of the bereaved had spouses who died of a chronic illness. These two groups were compared on three criteria of medical adjustment: physician office visits, feeling ill without contacting a physician, and use of psychotropic medications. The data indicated that the aged bereaved of a le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
2

Year Published

1979
1979
1995
1995

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(45 citation statements)
references
References 0 publications
3
39
1
2
Order By: Relevance
“…In a recent review Fasey (1990) drew atten-gave insufficient weight to measures of social tion to evidence in the literature of some adjustment (Faschingbauer et al, 1977). In a further review of the subject, Gerber et al (1975) found no evidence of any beneficial effect of anticipatory grief on the course of bereavement. This study showed that spouses did worse after chronic fatal illnesses, but outcome measures were unsophisticated and no psychological measurements were made.…”
Section: Anticipatory Griefmentioning
confidence: 88%
“…In a recent review Fasey (1990) drew atten-gave insufficient weight to measures of social tion to evidence in the literature of some adjustment (Faschingbauer et al, 1977). In a further review of the subject, Gerber et al (1975) found no evidence of any beneficial effect of anticipatory grief on the course of bereavement. This study showed that spouses did worse after chronic fatal illnesses, but outcome measures were unsophisticated and no psychological measurements were made.…”
Section: Anticipatory Griefmentioning
confidence: 88%
“…We reasoned that the 6-month point minimized these confounds but was still early enough in the bereavement to capture the quality of initial coping responses (Dyregrov & Matthiesen, 1991;Gerber, Rusalem, Hannon, Battin, & Arkin, 1975;Windholz, Marmar, & Horowitz, 1985). Somatic symptoms were assessed with an 18-item self-report checklist used in the Whitehall II study, a large scale study of morbidity among civil servants in London, England (Marmot et al, 1991;Stansfeld, Smith, & Marmot, 1993).…”
Section: Phase 2: Structured Grief Symptom Interview (6 Months)mentioning
confidence: 99%
“…Thus, although the death of a spouse is usually a traumatic life event, the aged are more prepared for such losses by experience of peers and may have a less severe reaction than the young. Data indicate that widows over 65 fare better than anticipated (Heyman and Gianturco, 1973), depending upon financial circumstances (Atchley, 1975), although widowers may do less well (Parkes et al, 1969;Gerber et …”
Section: Age and Stressmentioning
confidence: 97%